A report on The National Council of Community Mental Health Centers - Carlson, Robert J. (Journal of religion and health, 1981)
The National Council of Community Health Centers represents a professional development of great interest to clergy. Because mental health centers collaborate with community agencies and systems, their interventions on behalf of community mental health provide an occasion to work toward common goals. Their policy of shared responsibility with community leaders and consumers provides a unique opportunity for a practical integration of religious systems and the public arena. A number of pastors and mental health trained clergy are actively participating in this common effort on behalf of the nation's mental health.